Revisiting MSC expansion from critical quality attributes to critical culture process parameters. (August 2017) - Martin, Céline; Olmos, Éric; Collignon, Marie-Laure; De Isla, Natalia; Blanchard, Fabrice; Chevalot, Isabelle; Marc, Annie; Guedon, Emmanuel
Abstract : Highlights: An update on the latest advances regarding hMSC characterization and bioprocessing is proposed. Relationships exist between CQA of hMSC expanded for cell therapy and CQP used during expansion. Process design and bulk validation will need to integrate proteomic and cellular biology tools. Streamlining efforts are yet needed to hinder the final in vivo outcome for hMSC therapeutic use. Abstract: With over 300 clinical trials registered in 2013 and more than 20, 000 hits on the NCBI database, human multipotent stromal cells (hMSC) are widely used and studied as a model for tissue engineering and regenerative medicine. This review aims to provide a general update on the latest advances regarding hMSC characterization and bioprocessing. This analysis of the recent literature once again shows the intrinsic relationship between critical quality attributes (CQA) of hMSC expanded for cell therapy and critical process parameters (CQP) used during their expansion. It hence demonstrates that process design and bulk validation will need to integrate not only proteomic but also cellular biology tools to meet regulatory authority's requirements and limit process variability. The necessity for another streamlining effort is underlined to facilitate study comparison and settle the problematics hindering hMSC therapeutic use: the influences of cell sources, population heterogeneity and culture conditions on the final in vivo outcome.